Chronic kidney disease progression in patients with resistant hypertension subject to 2 therapeutic strategies: Intensification with loop diuretics vs aldosterone antagonists - Verdalles, U; Goicoechea, M; García de Vinuesa, S; Torres, E; Hernández, A; Verde, E; Pérez de José, A; Luño, J (Nefrologia : publicacion oficial de la Sociedad Espanola Nefrologia, 2020)
Actualy, there are few data about glomerular filtration rate (eGFR) drop in patients with resistant hypertension and how diferent therapies can modify chronic kidney disease progression (CKD). To evaluate CKD progression in patients with resistant hypertension undergoing 2diferent therapies: treatment with spironolactone or furosemide. We included 30 patients (21M, 9W) with a mean age of 66.3±9.1 years, eGFR 55.8±16.5ml/min/1.73 m , SBP 162.8±8.2 and DBP 90.2±6.2mmHg: 15 patients received spironolactone and 15 furosemide and we followed up them a median of 32 months (28-41). The mean annual eGFR decrease was -2.8±5.4ml/min/1.73 m . In spironolactone group was -2.1±4.8ml/min/1.73 m and in furosemide group was -3.2±5.6ml/min/1.73 m , P<0.01. In patients received spironolactone, SBP decreased 23±9mmHg and in furosemide group decreased 16±3mmHg, P<.01. DBP decreased 10±8mmHg and 6±2mmHg, respectively (P<.01). Treatment with spironolactone reduced albuminuria from a serum albumin/creatine ratio of 210 (121-385) mg/g to 65 (45-120) mg/g at the end of follow-up, P<.01. There were no significant changes in the albumin/creatinine ratio in the furosemide group. The slower drop in kidney function was associated with lower SBP (P=.04), higher GFR (P=.01), lower albuminuria (P=.01), not diabetes mellitus (P=.01) and treatment with spironolactone (P=.02). Treatment with spironolactone (OR 2.13, IC 1.89-2.29) and lower albuminuria (OR 0.98, CI 0.97-0.99) maintain their independent predictive power in a multivariate model. Treatment with spironolactone is more effective reducing BP and albuminuria in patients with resistant hypertension compared with furosemide and it is associated with a slower progression of CKD in the long term follow up.